ENVIRONMENT ACCOUNTING: A CURRICULUM MODEL TO INDIAN ACADEMIA - Muninarayanappa, M.; Amaladas, L. Augustin (European Scientific Journal, ESJ, 2014)
Business creates assets to self by using natural resources by creating social environmental liabilities by degradation of environment. Traditional double entry financial accounting is more concern about quantification of business transactions in terms of money. Traditional money measurement concept accounting is limited when it comes to measuring natural wealth degradation. We are behind the times… Jet pilots don‘t use rearview mirrors. If we want to account for the environment, it is necessary to look ahead. Developing future accountants who can measure quantitatively the environmental degradation depends on the present commerce and management teachers who have ability to understand and teach the methods to measure, costs related to environmental degradation. It is a pleasure, challenge and duty of the commerce and management faculty throughout the world in particular in India to understand the importance of implementation of environmental accounting as a part of university curriculum as a nation building exercise. The present paper aims to discuss the significance of environmental accounting in Indian university curriculum. The data required for the study have been collected from primary and various secondary sources. This research is descriptive in nature.Understanding reliable estimates of environmental damages, upstream/downstream costs of pollution, recovery from the market(carbon credit), cost of management activities, research and development costs, costs for social programs and costs for handling environmental damage will help commerce teachers to inculcate knowledge in commerce students and the government to implement the environmental accounting in the near future in India.